Hydrogen‐Bonded Supramolecular Polymer Adhesives: Straightforward Synthesis and Strong Substrate Interaction. (3rd May 2022) - Chen, Senbin; Li, Zeke; Wu, Yanggui; Mahmood, Nasir; Lortie, Frédéric; Bernard, Julien; Binder, Wolfgang H.; Zhu, Jintao
Abstract: High‐performance adhesives are of great interest in view of industrial demand. We herein identify a straightforward synthetic strategy towards universal hydrogen‐bonded (H‐bonded) polymeric adhesives, using a side‐chain barbiturate (Ba) and Hamilton wedge (HW) functionalized copolymer. Starting from a rubbery copolymer containing thiolactone derivatives, Ba and HW moieties are tethered as pendant groups via an efficient one‐pot two‐step amine‐thiol‐bromo conjugation. Hetero‐complementary Ba/HW interactions thus yield H‐bonded supramolecular polymeric networks. In addition to an enhanced polymeric network integrity induced by specific Ba/HW association, the presence of individual Ba or HW moieties enables strong binding to a range of substrates, outstanding compared to commercial glues and reported adhesives. Abstract : A straightforward synthetic strategy towards strong supramolecular adhesives is reported, based on a side‐chain barbiturate (Ba) and Hamilton wedge (HW) functionalized polymer. Specific Ba/HW interactions serve as cohesive domains to maintain polymeric network integrity, while molecular configuration of individual Ba or HW moieties linked onto substrates via diverse H‐bonding interactions, form adhesive domains and endow strong adherence.